Women’s Preparation to Encounter Flood Disaster in East Jakarta, Jakarta - ., Muzani; Irma, Asma; ., Vierza (GEOGRAFI, 2018)
The article aims to explore women’s level of preparedness in facing flood disaster in East Jakarta, Jakarta. This research was carried out from September 2016 to May 2017. Descriptive quantitative research method was used in the research. Based on the research results, it could be concluded that women’s level preparedness to encounter flood disaster in East Jakarta in 2013-2016 was under the ready category. On the knowledge parameter, the attitudes in the two areas are under the same category which is very ready. It indicates that the respondents have excellent knowledge on flood disaster. The parameter of emergency response plan is under the same category of almost ready. There are some indicators that show the low rate of the precaution for disaster preparation; emergency telephone numbers and addresses as well as the training of evacuation and first aids. The early warning system parameter shows the low results. For the affected area of flood disaster in 2013-2016, it is under the category of almost ready. In the area, there have been established some information sources through social media, and all citizens in the area are not entirely involved. Moreover, for the affected area of flood disaster in 2016 it is under the category of almost ready because the citizens are not familiar with the information of flood disaster early warning through social media. Moreover, in the parameter of sources mobilization, it is under the category of almost ready for low participation in the training of flood disaster early warning, skill and funding as well as logistic that the respondents could not prepare well.